STRATEGI MULTI- PLATFORM COMMUNICATION SPECIALIST DALAM MENINGKATKAN BRAND AWARENESS PT PREDIKT TANGGUH INDONESIA - Oetomo, Annisaa Larasati (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to explore multi – platform digital communication strategies by the communications specialist division of PT Predikt Tangguh Indonesia in effectively increasing the company’s brand awareness in this digital era. Instagram and LinkedIn are utilized to reach different target audiences, with adjusted communication approaches for each platform. This research uses a qualitative method, using data collection techniques such as in-depth interviews, content observation, documentation of social media activities, and literature review. In addition, digital metrics such as engagement rate, reach and growth are used as supporting indicators for analysis. The findings of multi-platform strategy reveal consistent cross-platform communication efforts significantly enhance brand visibility and audience engagement. The application of visual storytelling content personalization, audience segmentation, and optimization of posting times are key success factors. Furthermore, PT Predikt Tangguh Indonesia’s brand awareness is reinforced by distinctive color palette that makes the content easily recognizable and memorable to the public. This communication strategy not only boosts digital interaction but also strengthens the company’s image as an active, professional, collaborative institution that is committed to disaster preparedness issues.